Optimalisasi Pemasaran Usaha Mikro, Kecil dan Menengah (UMKM) Makanan Dengan Pemanfaatan Whatsapp - Syarif; Bakti Abu Birgantoro; Agus Hermawan; Mohammad Anwar Gani; Sugiyanto Sugiyanto; Ali Maddinsyah (Jurnal Pengabdian Masyarakat Madani, 2022)
This Community Service is entitled Optimizing the Marketing of Micro, Small, and Medium Enterprises / MSMEs (UMKM in Bahasa Indonesia) for Food by Utilizing Whatsapp Business on UMKM Jabar Juara Depok. The general purpose of this community service activity is to provide counseling, assistance, and training regarding marketing strategies for food MSME products that are effective and applicable to be implemented during the COVID-19 pandemic. The method used in the Community Assistance activity this time is the interview method, mentoring, and training on the use of WhatsApp business social media technology as a means of marketing food MSME products. The result of this community service activity shows that information sharing and technology transfer, as well as the participation of the government, the world of education, and other stakeholders in efforts to assist and develop MSMEs, are highly expected by MSME business actors in the field level. The conclusion of this community service activity in the difficult conditions such covid 19 pandemic, there are still concrete strategies that can be carried out by Food MSME business actors in order to optimize the marketing and sales of their products, including the use of the WhatsApp business application